Where Consumers Diverge from Others: Identity Signaling and Product Domains - Berger, Jonah; Heath, Chip (Journal of Consumer Research, 2007)
Abstract We propose that consumers often make choices that diverge from those of others to ensure that they effectively communicate desired identities. Consistent with this identity-signaling perspective, four studies illustrate that consumers are more likely to diverge from majorities, or members of other social groups, in product domains that are seen as symbolic of identity (e.g., music or hairstyles, rather than backpacks or stereos). In identity domains, participants avoided options preferred by majorities and abandoned preferences shared with majorities. The social group associated with a product influenced choice more in identity domains and when a given product was framed as identity relevant. People diverge, in part, to avoid communicating undesired identities.